Direct Role of a Viroid RNA Motif in Mediating Directional RNA Trafficking across a Specific Cellular Boundary - Qi, Yijun (American Society of Plant Biologists, 2004)
The plasmodesmata and phloem form a symplasmic network that mediates direct cell–cell communication and transport throughout a plant. Selected endogenous RNAs, viral RNAs, and viroids traffic between specific cells or organs via this network. Whether an RNA itself has structural motifs to potentiate trafficking is not well understood. We have used mutational analysis to identify a motif that the noncoding Potato spindle tuber viroid RNA evolved to potentiate its efficient trafficking from the bundle sheath into mesophyll that is vital to establishing systemic infection in tobacco (Nicotiana tabacum). Surprisingly, this motif is not necessary for trafficking in the reverse direction (i.e., from the mesophyll to bundle sheath). It is not required for trafficking between other cell types either. We also found that the requirement for this motif to mediate bundle sheath-to-mesophyll trafficking is dependent on leaf developmental stages. Our results provide genetic evidence that (1) RNA structural motifs can play a direct role in mediating trafficking across a cellular boundary in a defined direction, (2) the bundle sheath–mesophyll boundary serves as a novel regulatory point for RNA trafficking between the phloem and nonvascular tissues, and (3) the symplasmic network remodels its capacity to traffic RNAs during plant development. These findings may help further studies to elucidate the interactions between RNA motifs and cellular factors that potentiate directional trafficking across specific cellular boundaries.